PERAN PEKERJA SOSIAL BAGI PENYANDANG DISABILITAS FISIK MELALUI TERAPI PSIKOSOSIAL DI SENTRA WIRAJAYA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study focuses on understanding the role of social workers and the impact of psychosocial therapy on the well-being of people with physical disabilities at Sentra Wirajaya. This study uses a qualitative approach with the aim of gaining an in-depth understanding of the role of social workers in improving the well-being of people with physical disabilities through psychosocial therapy at Sentra Wirajaya Makassar. The results of this study indicate that social workers at Sentra Wirajaya Makassar play a strategic and multidimensional role in improving the well-being of people with physical disabilities. Through their functions as facilitators, counselors, companions, and service connectors, social workers are able to help clients build self-confidence, increase independence, and expand access to various social services. The psychosocial therapy implemented, such as counseling, social skills training, and organizational activities, has a positive impact on clients' psychological and social conditions, including increased self-confidence, motivation, and social participation. However, challenges such as low internal motivation among clients, limited facilities, and a shortage of professional staff remain obstacles to optimizing the program. The implications of these findings are: 1) This study reinforces the concept that social workers play a multidimensional role in improving the well-being of individuals with physical disabilities. 2) Institutions need to improve the consistency of schedules and the capacity of staff to ensure that psychosocial therapy programs run optimally. 3) Further research is recommended to evaluate the long-term effectiveness of psychosocial therapy programs and analyze factors influencing client motivation.